2003
DOI: 10.1385/endo:21:3:209
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Effects of Acute Hemiovariectomy on Steroid Hormone Secretion by the In Situ Ovary

Abstract: The acute effects of hemiovariectomy on progesterone, testosterone, estradiol, and luteinizing hormone (LH) concentrations in serum were studied in rats under the following experimental conditions: control, shamoperated (left or right), hemiovariectomized, bilateral adrenalectomized, and hemiovariectomized plus bilateral adrenalectomized. One-hour after surgery, the concentration of progesterone and testosterone in the serum of right-side sham-operated rats was significantly higher than in control animals. Tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
2
26
2
Order By: Relevance
“…The sensitivity of the left and right ovaries is also different. This is in agreement with the findings of other authors who have shown an asymmetry in the behaviour of the left ovary in relation to the right one according to the characteristics of the neural stimulus applied (Dominguez et al 1989, Barco et al 2003, Morán et al 2005. Besides, the ganglion presence in the preparation and good conservation of its structure is kept until the end of the incubation period, which shows the excellent viability of the incubation system.…”
Section: Discussionsupporting
confidence: 92%
“…The sensitivity of the left and right ovaries is also different. This is in agreement with the findings of other authors who have shown an asymmetry in the behaviour of the left ovary in relation to the right one according to the characteristics of the neural stimulus applied (Dominguez et al 1989, Barco et al 2003, Morán et al 2005. Besides, the ganglion presence in the preparation and good conservation of its structure is kept until the end of the incubation period, which shows the excellent viability of the incubation system.…”
Section: Discussionsupporting
confidence: 92%
“…In the rat the left ovary releases more ova than the right-side one . The left ovary has been reported to have a greater capacity to secrete progesterone (Barco et al, 2003;Flores et al, 2005) and testosterone (Flores et al, 2006) in response to hemicastration. On the basis of the asymmetry in the number of ova shed and in the response of the left and right ovary to acute hemiovariectomy, asymmetry in the innervation of the left and right ovary has been postulated.…”
Section: Discussionmentioning
confidence: 99%
“…Asymmetry of the rodent ovary includes difference in the venous drainage and functional asymmetry of the gonad in response to acute hemicastration (Barco et al, 2003;Flores et al, 2005) or to transection of the nerves supplying the gland (Chavez and Dominguez, 1994;Chavez et al, 1987Chavez et al, , 1989. Concerning asymmetry at the level of cerebral structures involved in the control of ovarian functions, observations indicate both biochemical and functional asymmetry of hypothalamic and temporolimbic structures (see for review Gerendai and Halász, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we showed that compared to cyclic sham-operated animals, acute extirpation of the left or right ovary results in changes in estradiol, progesterone and testosterone serum levels, and that these changes depend on the hormone studied and the day of the cycle when surgery was performed; indicating an asymmetric ability for hormone release by the ovaries [36-38]. Gerendai et al [39] did not observe such effects when performing ULO to adult rats nine days after surgery.…”
Section: Discussionmentioning
confidence: 99%